The Benefits of Breastfeeding - Cassie C. Rowe; Karla P. Shelnutt; Gail P. A. Kauwell (EDIS, 2012)
Experts agree that breast milk is the best food for babies for the first six months of life. It is a healthy choice that offers many benefits for both mother and baby. Breast milk is an excellent source of nutrients and antibodies, and breastfeeding helps to create a strong bond between mother and child. For the mother, it may help to lose weight gained during pregnancy and reduce the chances of developing common diseases like diabetes and breast and ovarian cancer. Breastfeeding is also economical, convenient, and natural. This 5-page fact sheet informs new mothers about why breastfeeding is a great choice. Written by Cassie C. Rowe, Karla P. Shelnutt, and Gail P. A. Kauwell, and published by the UF Department of Family, Youth and Community Sciences, March 2012.